Self-assembled peptide microspheres for sustainable release of sulfamethoxazole. Issue 45 (19th April 2016) - Pramanik, Apurba; Paikar, Arpita; Das, Tanmay; Maji, Krishnendu; Haldar, Debasish
Abstract : Porous peptide microspheres have been used for the loading and sustained release of the bacteriostatic antibiotic sulfamethoxazole. Abstract : The self-assembly of two peptides Boc-Phe-Aib-Gabu-OMe1 and Boc-Tyr-Aib-Gabu-OMe2 (Aib = α-aminoisobutyric acid, Gabu = γ-aminobutyric acid) containing a core of a conformationally rigid achiral amino acid and a conformationally flexible achiral amino acid at the C-terminus was studied to fabricate a sustainable delivery vehicle. From X-ray crystallography, peptide1 with the Phe residue adopts a type II turn-like structure whereas the Tyr analogue2 adopts a type II′ turn-like structure. However, peptide1 self-associates to form four membered ring-like porous structures through multiple intermolecular hydrogen bonds but peptide2 self-associates to form five membered ring-like porous structures by intermolecular hydrogen bonds. Field emission scanning electron microscopy (FE-SEM) revealed that both the peptides exhibit microsphere morphologies. Further, these microspheres were loaded with the bacteriostatic antibiotic sulfamethoxazole. The growth inhibition of E. coli is greater for the peptide1 -sulfamethoxazole formulation than for the peptide2 -sulfamethoxazole formulation which indicates that the formulation leads to sustained release of the encapsulated drug. The peptide2 microspheres slowly release the encapsulated sulfamethoxazole, more so than the peptide1 microspheres.